2016
DOI: 10.1016/j.adolescence.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotional reactivity moderates the relations between family cohesion and internalizing and externalizing symptoms in adolescence

Abstract: Lower family cohesion is associated with adolescent internalizing and externalizing problems. However, there are likely individual differences in youth's responses to family processes. For example, adolescents higher in negative emotional reactivity, who often exhibit elevated physiological responsivity to context, may be differentially affected by family cohesion. We explored whether youth's negative emotional reactivity moderated the relation between family cohesion and youth's symptoms and tested whether fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 92 publications
(98 reference statements)
3
35
0
Order By: Relevance
“…In partial support of this hypothesis aggression at T1 was associated with family cohesion at T2 in which greater levels of child aggression contributed to poorer family cohesion over time. This outcome is in-line with previous literature showing that adolescent aggression contributes to decreases in family cohesion (Conger et al, 1994; Henderson et al, 2006; Rabinowitz, 2016). Conversely, family cohesion at T1 was not associated with aggression at T2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In partial support of this hypothesis aggression at T1 was associated with family cohesion at T2 in which greater levels of child aggression contributed to poorer family cohesion over time. This outcome is in-line with previous literature showing that adolescent aggression contributes to decreases in family cohesion (Conger et al, 1994; Henderson et al, 2006; Rabinowitz, 2016). Conversely, family cohesion at T1 was not associated with aggression at T2.…”
Section: Discussionsupporting
confidence: 92%
“…During adolescence, family cohesion and adolescent behavior are particularly intertwined. Adolescence is a period of heightened conflict in the family, in which adolescent aggression and hostility contribute to increases in family conflict and decreases in family cohesion (Conger, Ge, Elder, Lorenz, & Simons, 1994; Henderson, Dakof, Schwartz, & Liddle, 2006; Rabinowitz, Osigwe, Drabick, & Reynolds, 2016). Poor family functioning during adolescence, including low family cohesion and greater disorganization, is associated with greater adolescent drinking and substance use (Bray, Adams, Getz, & Baer, 2001; Foxcroft & Lowe, 1991; Gutman et al, 2011; Lloyd-Richardson, Papandonatos, Kazura, Stanton, & Niaura, 2002; Smart et al, 1990; Wagner et al, 2010).…”
Section: Aggression Family Cohesion and Substance Usementioning
confidence: 99%
“…In this study, eight items assessing depression/anxiety and nine items assessing emotionally reactive problems were used, and the average scores of each subscale were analyzed. While the term “emotionally reactive problems” has been used as a label for emotional regulation processes that play a role in predicting other outcomes, such as internalizing and externalizing behaviors (e.g., Kalvin, Bierman, & Gatzke-Kopp, 2016; Rabinowitz, Osigwe, Drabick, & Reynolds, 2016), the CBCL Emotionally Reactive Problems subscale assesses a behavioral outcome: child internalizing problems that are emotional in nature (Ivanova et al, 2011). Coefficient alphas for depression/anxiety and emotionally reactive problems, respectively, were .72 and .74.…”
Section: Methodsmentioning
confidence: 99%
“…Studies exploring patterns of plasticity in adolescence are mixed. While some found that differential susceptibility to positive and negative parenting extended to influence EB in adolescence and even young adulthood (Chhangur et al., ; Nikitopoulos et al., ), others found diathesis‐stress to best characterize EB development in adolescence (Belsky & Pluess, ; Rabinowitz, Osigwe, Drabick, & Reynolds, ). Interestingly, a recent review found that differential susceptibility predicted adolescent EB and substance use depending on the timing of temperament and family environment assessed (Rioux et al., ).…”
mentioning
confidence: 99%